Opportunities and threats related to labour market globalization - Majkut, R. (Економічний вісник Національного гірничого університету, 2009)
The article considers different aspects of globalization and its consequences for national labour markets. The main forces of globalization process are analyzed. The main factors of the process are explored. The author gave his advices on investment in human capital and innovation technique to diminish and smooth down the negative influence of globalization on a labour market.

Стаття розглядає різні аспекти глобалізації та її наслідки для національних ринків праці. Проаналізовано основні рушійні сили процесу глобалізації. Досліджено основні фактори самого процесу. Автором надано рекомендації стосовно інвестицій в людській капітал і розвиток інноваційних технологій для зменшення і пом’якшення негативного впливу глобалізації на ринок праці.
Keywords: інноваційна діяльність; ринок праці